Autoantibodies and immune complexes to oxidation-specific epitopes and progression of aortic stenosis: Results from the ASTRONOMER trial. (May 2017) - Capoulade, Romain; Chan, Kwan L.; Mathieu, Patrick; Bossé, Yohan; Dumesnil, Jean G.; Tam, James W.; Teo, Koon K.; Yang, Xiaohong; Witztum, Joseph L.; Arsenault, Benoit J.; Després, Jean-Pierre; Pibarot, Philippe; et al.
Abstract: Background and aims: Elevated levels of lipoprotein(a) [Lp(a)] and oxidized phospholipids on apolipoprotein B-100 (OxPL-apoB) predict the progression of pre-existing mild-to-moderate calcific aortic valve stenosis (CAVS). Whether indirect markers of oxidation-specific epitopes (OSE) are also predictive is not known. The association between IgG and IgM autoantibodies and malondialdehyde-modified low density lipoprotein (MDA-LDL) and IgG and IgM apolipoprotein B immune complexes (apoB-IC), and the hemodynamic progression rate of CAVS was determined in the ASTRONOMER (Aortic Stenosis Progression Observation: Measuring Effects of Rosuvastatin, NCT00800800) trial. Methods: Plasma levels of IgG and IgM MDA-LDL and apoB-IC were measured in 220 patients with mild-to-moderate CAVS from the ASTRONOMER trial. The endpoint of this study was the progression rate of CAVS, measured by the annualized increase in peak aortic jet velocity (Vpeak ) over a median follow-up of 3.5 [2.9–4.5] years. Results: There was no difference in the progression rate of CAVS across tertiles of IgG and IgM MDA-LDL and apoB-IC levels (all p > 0.05). After multivariable analysis, no marker reached significance level to predict faster CAVS progression or need for aortic valve replacement (all p > 0.05). There was no interaction between the OSE antibody titers and plasma levels of Lp(a) or OxPL-apoB, as well as age, with regards to the progression rate of CAVS. Conclusions: Autoantibody titers to MDA-LDL and apoB-IC, which are an indirect measurement of OSE, unlike direct measurements of OxPL-apoB or their major lipoprotein carrier Lp(a), do not predict the progression of CAVS or need for AVR. Highlights: Plasma levels of IgG and IgM MDA-LDL and apoB-IC were measured in 220 patients with aortic stenosis. There was no difference in progression rate across tertiles of IgG and IgM MDA-LDL and apoB-IC levels. After multivariable analysis, no marker reached significance level to predict need for aortic valve replacement (AVR).